The Effect of the Increasing Doses of Vermicompost Applications to Soil on Some Nutrient Concentrations in Olive (Olea europaea L.) Leaves - Ayşe Nur Coşkun; Ali Sümer (Journal of Advanced Research in Natural and Applied Sciences, 2023)
This research was conducted on young olive (Olea europaea L.) trees in a private cultivation land located in Bozkoy closed to Geyikli District of Çanakkale Province, Türkiye in the year 2018. The study aimed to investigate the effects of different doses of vermicompost [(control) 0, 2, 4, 6 kg tree-1] on macro and micro nutrient elements of olive trees. Randomized complete block design was established applying four doses with 5 replications. Vermicompost was applied to the soil in a depth of 15-20cm under the crown projection area. During the fruit maturity stage, the leaf samples were collected from annual shoot tip leaves. Macro nutrient element concentrations namely nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), and magnesium (Mg) stayed inside the limit values upon applications of increasing doses of vermicompost. While the changes were statistically non-significant. Even though, this research was an annual study comprised on a single year, where N was in an increasing trend and 2 kg tree-1 was found to be the most effective dose of vermicompost on N values (17.13 g kg-1). Among the leaf micro nutrient elements, statistically significant increases were obtained by 2 kg tree-1 on copper (Cu) (31.32 mg kg-1), on manganese (Mn) (50.77 mg kg-1), and 6 kg tree-1, on zinc (Zn) (21 mg kg-1); while a decrease was ob-served on iron (Fe) concentration by 6 kg tree-1 (100.88 mg kg-1). Micro nutrient elements remained under the limit of toxic effect upon all the applications. The dose 2 kg tree-1 was determined to be the most suitable one in terms of both macro and micro element concentrations under such trial circumstances.